Thyroid fine needle aspiration biopsy results before and during the COVID-19 pandemic: From a single-center perspective - Babayeva, Afruz; Coskun, Meric; Yalcin, Mehmet Muhittin; Uzun, Arzu; Inan, Mehmet Arda; Eroglu Altinova, Alev; Akturk, Mujde; Karakoc, Mehmet Ayhan; Balos Toruner, Fusun; Yetkin, Ilhan (Annals of Medical Research, 2023)
Aim: One of the effects of the COVID-19 pandemic on the healthcare system has been the postponement of elective procedures. We aimed to investigate how the COVID-19 pandemic has affected our thyroid fine-needle aspiration biopsy (FNAB) results.Materials and Methods: The distribution of cytology results during the 16.5 months of the pandemic was compared with the pre-pandemic period by The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) diagnostic categories.Results: The number of FNABs performed during the pandemic period decreased by 27.3% compared to the pre-pandemic period in our center, in line with the recommendations (1,197 to 327 diagnostic FNABs). Benign biopsy results decreased during the pandemic period compared to the pre-pandemic period (77.3% to 49.5%, p
Keywords: SARS-COV2 infection; COVID 19 pandemic; Thyroid nodule; Thyroid fine-needle aspiration; Thyroid cancer